Journeys of Soviet things - Rajagopalan, Sudha, author.
1 online resource.
Keywords: "At the intersection of history, material culture studies and post-socialist memory studies, Journeys of Soviet Things is an oral history of socialist globalisation constructed around the journeys of Cold War era Soviet objects in India and Cuba. During the Cold War, an important means to perpetuate Soviet ideals of modernisation and anti-imperialist solidarity across the world was the circulation of 'banal' objects, produced in the Soviet Union and purchased, awarded and gifted for use in homes across the world. Based on oral accounts of Indian and Cuban interlocutors, this book examines the itineraries of Soviet objects such as cars, washing machines, cameras, books, nesting dolls, porcelain, and many other things. Explored this way, the Cold War is a matter of personal, affective, everyday experience. At the same time, by indicating the cohabitation of things in their home from around the world, interlocutors also go on to undercut simple geopolitical binaries that pit Soviet against American techno-politics. Accounts of Soviet objects in India and Cuba reveal a bricolage of preferences that crisscrossed ideological dualities of East vs West, communist vs. capitalist, making for an alternative cosmopolitanism that was in equal measure shaped by personal, local and national histories and experiences. This book will appeal to researchers and students interested in Cold War history, the history of transnational solidarities and Soviet material culture"--